Biodessulfurização do biogás gerado no processo de digestão anaeróbia da estação de tratamento de efluentes de uma indústria cervejeira - Guerrero, Renata de Bello Solcia [UNESP] (2015)
Currently, the use of energy-rich gases such as biogas generated in wastewater treatment plants is becoming more attractive due environmental and economic constraints associated with fossil fuels. However, the use of such gases is clearly limited by the presence of reduced sulfur compound, such as, hydrogen sulfide (H2S), present in relatively high concentrations (500-20,000 ppmv). In this work, experiments were carried out in order to study H2S removal from biogas produced from an anaerobic reactor of the wastewater treatment plant of a Brewery Industry (Araraquara, SP) using a lab-scale biotrickling filter, in anoxic conditions. A consortium of nitrate-reducing, sulfide-oxidizing microorganisms, obtained from the anaerobic sludge of the same anaerobic reactor was immobilized on open-pore polyurethane foam. Some operational parameters were investigated, such as, the effect of temperature, nitrate concentration (final electron acceptor) in the trickling medium, the empty bed residence time (EBRT), and the trickling liquid velocity (TLV). The development of biofilm utilizing microorganisms from UASB reactor showed a high performance. The results showed that nitrate and nitrite (final electron acceptors) depletion on the trickling medium resulted in remarkable instability of the system, with consequent decrease on the removal efficiency (RE), which came to drop to 0%. The biotrickling filter showed better performance in the temperature range between 31 - 42 °C (RE) = 91.8 ± 5.5%), wherein at 22 °C, RE dropped to 39% (inlet load (L) = 5.3 g S-H2S m-3 h-1, EBRT = 2.9 min). The TLV effect (4.4, 7.4 and 11 m h-1) was significant only for EBRT of 1.6 min, in which RE decreased from 50.9% (4.4 m h-1) to 33.7% (7.3 m h-1). It was also observed that it is possible to increase the RE fragmenting the gas stream into two parts and feeding at different points of the biofilter. For a biogas/H2S gas stream of...